2016
DOI: 10.1007/s13566-016-0273-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of stereotactic body radiation therapy (SBRT) with fiducial tracking for inoperable stage I non-small cell lung cancer (NSCLC)

Abstract: BackgroundStereotactic body radiation therapy (SBRT) for stage I non-small cell lung cancer (NSCLC) is considered standard of care in the medically inoperable patient population. Multiple methods of SBRT delivery exist including fiducial-based tumor tracking, which allows for smaller treatment margins and avoidance of patient immobilization devices. We explore the long-term clinical outcomes of this novel fiducial-based SBRT method.MethodsIn this single institutional retrospective review, we detail the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 29 publications
3
25
1
Order By: Relevance
“…Difference of selection criteria of included patients and different fractionation scheme precludes direct comparison between studies, however, the incidence of RIRF in our study was lower than those in previous studies, in general. Recently, Lischalk et al reported long-term outcome of non-small cell lung cancer patients treated with Cyberknife® using fiducial tracking [25]. Although their incidence of rib fracture was higher (21.4% in 2 years) than that in our study, it was relatively lower than those in most other studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Difference of selection criteria of included patients and different fractionation scheme precludes direct comparison between studies, however, the incidence of RIRF in our study was lower than those in previous studies, in general. Recently, Lischalk et al reported long-term outcome of non-small cell lung cancer patients treated with Cyberknife® using fiducial tracking [25]. Although their incidence of rib fracture was higher (21.4% in 2 years) than that in our study, it was relatively lower than those in most other studies.…”
Section: Discussioncontrasting
confidence: 80%
“…The pooled estimate for 5-year OS for biopsy-proven disease (n ¼ 8101) was not significantly different 17,19,25,27,28,[32][33][34][35]38,39,41,42,[44][45][46][48][49][50]52,53,55,59 respectively (Fig 3). For 3-year OS, there was no difference between clinical disease 19 21,26,30,31,36,40,46,49,51,54,56,58,59 for biopsy-proven disease (n ¼ 998 and n ¼7249), respectively.…”
Section: Oncological Outcomes Of Noncomparative Studiesmentioning
confidence: 91%
“…Therefore, the identification of methods to improve the survival rate of patients with NSCLC has become an important task [2]. At present, treatment for NSCLC includes surgery, chemotherapy, and radiotherapy [3], of which radiotherapy is the main approach [4]. Nevertheless, despite the great efforts that have been exerted to develop radiation therapies for NSCLC patients, the 5-year overall survival rate still remains less than 15% [1, 5].…”
Section: Introductionmentioning
confidence: 99%